Color scheme for decoration of an eight-roomed house - Westgate, Helen Clara (My University, 1907)
Introduction: The relation of color to light is much the same as that of music to sound. Color has its many tones, its long scales of tints and shades, its true and its false chords. Mere sound is not particularly pleasing to us, but allow the sound to be developed into its highest forms, music, and the whole soul is thrilled. Do in light our enjoyment reaches its heighth when we view the varied hues of the sunset, or the beauties of art unfolded flower. Hence it seems very appropriate to designate color as “the music of light.” What a dull prosaic would indeed this would be, were there no soft green forests of varying shades to rest our eyes, no new wonders in the form of unfolding blossoms always giving evidence of the inexhaustible resources of nature. Nature uses splendid judgement in the selection of colors. No glaring masses of solid color, unbroken by tint or shade are ever used…
Citation: Westgate, Helen Clara. Color scheme for decoration of an eight-roomed house. Senior thesis, Kansas State Agricultural College, 1907.
Morse Department of Special Collections
Keywords: Color Scheme; Home Decorations; Color in the Home; The Employment of Colors; Theses; Manuscripts (documents)